1984
DOI: 10.1002/ddr.430040109
|View full text |Cite
|
Sign up to set email alerts
|

CGS 9896: A nonbenzodiazepine, nonsedating potential anxiolytic

Abstract: Various behavioral and neurochemical studies indicate that CGS 9896 may represent a novel, nonsedating anxiolytic. This substance, chemically related to the benzodiazepine antagonist CGS 8216, was effective in conflict and nonconflict models of anxiety. At the same time, CGS 9896 did not disrupt rotorod performance or decrease levels of responding in various operant procedures. In fact, CGS 9896 reversed the deficit in rotorod behavior produced by diazepam. CGS 9896 did not generalize to diazepam in rats train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Wood et al (19) reported that the non sedating benzodiazepine agonist/antagonist CGS9896 had a GABA ratio of 1 (24) exert an agonistic action on one class of benzodiazepine receptors and an antagonistic action on another class. It has been suggested that these compounds have affinities for the benzodiazepine receptors of the cerebellum that are different from those for the cerebral cortex receptors and that they have good separation ratios between their anxiolytic action and side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Wood et al (19) reported that the non sedating benzodiazepine agonist/antagonist CGS9896 had a GABA ratio of 1 (24) exert an agonistic action on one class of benzodiazepine receptors and an antagonistic action on another class. It has been suggested that these compounds have affinities for the benzodiazepine receptors of the cerebellum that are different from those for the cerebral cortex receptors and that they have good separation ratios between their anxiolytic action and side effects.…”
Section: Discussionmentioning
confidence: 99%
“…CGS8216 blocks the anticonvulsant effects of CGS9896 (Bennett and Petrack, 1984). In our experiments, it completely and rapidly antagonized the suppressant action of CGS 9896 on absence-like seizures, and its effect was more persistent than that of Ro 15-1788 on the anti-petit mal effect of diazepam.…”
Section: Discussionmentioning
confidence: 65%
“…This is similar to the rank order of potency of these compounds in the yohimbine-induced seizure model. Similarly, the nonbenzodiazepine anxiolytics, namely, CGS 9896, CL 218,872, zopiclone, and tracazolate have been shown to interact with the benzodiazepine-GABA receptor complex [Olsen, 19811 and have all shown anxiolytic properties as anticonvulsants and in conflict models [Lippa et al, 1979a;Patel and Malick, 1982;Bernard et al, 1983Bernard et al, , 1985Goldberg et al, 1983;Julou et al, 1983Julou et al, , 1985Bennett and Petrack, 1984;Malick et al, 1984;Patel et al, 19851. However, CGS 9896 has shown weak anticonvulsant activity in mice in the pentylenetetrazol [Brown et al, 19841 and picrotoxin assays [Pellow, 19851.…”
Section: Discussionmentioning
confidence: 98%